Внесок військових у козакознавчі студії на території Південної України у другій половині ХІХ – на початку ХХ ст. - Музичко, О. (Чорноморська минувшина, 2019)
Метою цієї статті є висвітлення процесу дослідження та популяризації на початку ХХ ст. історії козацьких формувань представниками офіцерського складу армії Російської імперії, які служили у полках, що дислокувалися на території Південної України (Одеська військова округа), або перебували тут у відставці. Нашим завданням є намітити коло цих осіб, встановити відповідні факти їх біографій, порівняти погляди на козацтво та підходи до популяризації історичних фактів, виявити чинники, що впливали на процес пізнання, співвіднести їх погляди з сучасними підходами і загалом актуалізувати тогочасний досвід. The purpose of this article is to study how officers of the army of the Russian Empire of the Odesa Military District explored and popularized the history of the Cossacks in the early twentieth century. Our task is to establish the circle of these individuals, establish the relevant facts of their biographies, compare views on the Cossacks and approaches to popularizing historical facts, identify the factors that influenced the cognition process, correlate their views with modern approaches and update the experience of history. The interest on the part of the military in the history of the Cossacks was recorded by us in almost all the main centers of the development of historical thought in Ukraine (except Kherson and Elisavetgrad). It is concluded that the attention of military historians was attracted by various Cossack troops, but mainly Ukrainian, Zaporozhye, and Russian, Don. The main motive for the officers to study the history of the Cossacks was not only scientific, but also the task of educating the patriotism of the military. The great historian of the Cossacks, the representative of the neo-romantic, populist movement in the historiography of D.I. Yavornitsky. All authors perceived the various groups of the Cossacks as branches of a single family of Cossacks. But the works of P.N. Andrianova and A.G. Avchinnikov contributed to the formation of the image of the Ukrainian Cossacks as a unique historical phenomenon, which was different from the Russian Cossacks. The texts of the officers expressed a whole range of assessments of the history of the Ukrainian and Russian Cossacks, but apologetization, that is, the protection of Cossacks from a negative historiographic tradition, generally prevailed. The authors made a lot of efforts to combine loyalty to the Romanov dynasty and the freedom-loving Cossack freemen. Целью этой статьи является исследование того как офицеры армии Российской империи Одесского военного округа исследовали и популяризировали историю казаков в начале ХХ века. Нашей задачей является установление круга этих лиц, установление соответствующих фактов их биографий, сравнить взгляды на казачество и подходы к популяризации исторических фактов, выявить факторы, которые влияли на процесс познания, соотнести их взгляды с современными подходами и актуализировать опыт истории. Сделан вывод о том, что внимание военных историков привлекли различные казаческие войска, но главным образом, украинское, запорожское, и российское, донское. Основной мотив того, что офицеры изучали историю казаков был не только научный, но и задача воспитания патриотизма у военных. Большое влияние на формирование соответствующего сегмента исторических представлений и на тексты имел выдающийся историк казаков, представитель неоромантического, народнического, течения в историографии Д.И. Яворницкий. Все авторы воспринимали различные группы казачества как ветви единой семьи казаков. Но труды П.Н. Андрианова и А.Г. Авчинникова способствовали формированию образа украинского казачества как уникального исторического явления, который отличался от российских казаков. В текстах офицеров было высказано целый спектр оценок истории украинского и российского казачества, но в целом преобладала апологетизация, то есть защита казаков от негативной историографической традиции. Авторы сделали много усилий, чтобы соединить лояльность к династии Романовых и свободолюбивой казаческой вольницей.